Correlation between refractive state, corneal thickness, and keratometry in ametropic patients. Issue 5 (September 2020) - Rosenblatt, Amir; Mimouni, Michael; Sela, Tzahi; Munzer, Gur; Varssano, David; Sorkin, Nir
Purpose: To analyze the correlation between age, gender, refractive error, keratometry, and corneal thickness in a large group of subjects. Methods: This study is a retrospective analysis of patients who underwent refractive surgery between January 2000 and February 2015 at Care Vision Refractive Clinic, Tel Aviv, Israel. Patient demographics, subjective refraction, pachymetry, and average keratometry were collected. Results: Overall, 51, 113 eyes of patients averaging 28.8 ± 9.3 years of which 53.9% were males were included. Average keratometry, spherical equivalent and cylindrical error differed significantly between male and female subjects (p < 0.001), while pachymetry did not (p = 0.332). In myopic eyes, correlations between age, pachymetry, average keratometry, spherical equivalent, and cylindrical error were all statistically significant except for the correlation between age and either pachymetry (p = 0.462) or spherical equivalent (p = 0.016). All correlations found were negligible or small (|r|= 0.003 to 0.141). In hyperopic eyes, correlations between age, pachymetry, average keratometry, spherical equivalent, and cylindrical error were all statistically significant except for the correlation between average keratometry and either pachymetry or cylindrical error (p = 0.344 or p = 0.274, respectively). All correlations found were negligible or small, except for a moderate correlation found between age and cylindrical error (r = 0.365). Conclusion: Refractive state, pachymetry, and keratometry of refractive surgery candidates are mostly weakly correlated.